INNOVATIVE ENGLISH TEACHING STRATEGIES: IMPLEMENTING TASK-BASED LANGUAGE TEACHING IN JUNIOR HIGH SCHOOL CURRICULUM - Leroy Holman Siahaan; Yon A E (University of Kuningan, 2024)
Task-Based Language Teaching has gained popularity as an effective approach in language education. It focuses on providing learners with authentic, purposeful tasks that mirror real-world communication situations. In this paper, we explore the potential of developing Task-Based Language Teaching into English Speaking Teaching materials. We discuss the benefits of using task-based activities for improving speaking skills and how they can be integrated into English speaking teaching materials. We also examine the challenges that may arise in the development process and provide recommendations for creating effective task-based English speaking teaching materials An educator's understanding of teaching methods determines the success of students in understanding the material by the teacher in class. However, facts in the field show that not all teachers can understand in determining relevant teaching methods to be used in classroom teaching. Especially in language teaching, good teaching skills are seen from the selection of methods that are relevant and appropriate to the learning objectives. Regarding the selection of relevant teaching methods. The method used in this research is the R&D (Research and Development) method which aims to develop Task Based Language Teaching (TBLT) based English teaching materials. Based on the explanation above, it can be concluded the classroom so that learning can be realized. Therefore, this requires a teaching method that can accommodate teachers in the classroom, and can help students learn. One method that can be used in language teaching is the TBLT-based teaching method or task-based teaching method. The purpose of research and development of English teaching materials based on TBLT or task-based teaching methods focuses on students understand the material well and students are expected to be able to become risk takers in carrying out tasks, become communicative individuals, and be able to complete tasks by building interactions, relationships, and can collaborate well with their friends. Keywords: learning module; English grammar; writing skills; junior high school students; research and development (R&D)